2018
DOI: 10.1093/nar/gky014
|View full text |Cite
|
Sign up to set email alerts
|

Complete genomic and transcriptional landscape analysis using third-generation sequencing: a case study of Saccharomyces cerevisiae CEN.PK113-7D

Abstract: Completion of eukaryal genomes can be difficult task with the highly repetitive sequences along the chromosomes and short read lengths of second-generation sequencing. Saccharomyces cerevisiae strain CEN.PK113-7D, widely used as a model organism and a cell factory, was selected for this study to demonstrate the superior capability of very long sequence reads for de novo genome assembly. We generated long reads using two common third-generation sequencing technologies (Oxford Nanopore Technology (ONT) and Pacif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
141
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(160 citation statements)
references
References 55 publications
12
141
0
7
Order By: Relevance
“…One main advantage of RNAseq is that it is quantitative, and with standards it is now possible to measure >4000 mRNAs in yeast cells to absolute levels, with it being found that mRNA copy number per cell generally varies across two orders of magnitude, from 1 to 100 per cell. RNAseq is traditionally done using next‐generation sequencing, but recently it has been shown that is possible to use nanopore sequencing technology not only to obtain long DNA sequences required for genome assembly, but also for measuring mRNA levels …”
Section: Systems Biologymentioning
confidence: 99%
“…One main advantage of RNAseq is that it is quantitative, and with standards it is now possible to measure >4000 mRNAs in yeast cells to absolute levels, with it being found that mRNA copy number per cell generally varies across two orders of magnitude, from 1 to 100 per cell. RNAseq is traditionally done using next‐generation sequencing, but recently it has been shown that is possible to use nanopore sequencing technology not only to obtain long DNA sequences required for genome assembly, but also for measuring mRNA levels …”
Section: Systems Biologymentioning
confidence: 99%
“…Another great advantage of Nanopore technology is that unique protocols for direct RNA sequencing have been developed, meaning that RNA viruses could be analyzed right away, without reverse transcription [192,193]. Even more, depending on the experiment objective, either differential RNA sequencing (dRNA-Seq) or mRNA could be investigated, the latter being achieved by ligating an adapter only to the poly-A tail, thus allowing for transcriptome analysis [192,194]. Direct RNA-Seq helps avoid distortions of fragments' representation [195] in the sample, revolutionizing the approach to studying RNA-viruses and the intricacies of their life cycle [196].…”
Section: Long Read Sequencingmentioning
confidence: 99%
“…To obtain mRNA counts that were uncorrelated to gene length, the residual of a linear model, based on ORF lengths as the response variable and mRNA counts as the explanatory variable, was used as the corrected response variable (Fig S1-4). By testing whether the introduced correction could potentially remove biological signal associated with gene length, using data from whole molecule RNA sequencing that does not rely on short-read assembly 80 , no correlation between gene length and its expression was found (Pearson's r = -0.08, p -value < 1e-6; Fig S1-8).…”
Section: Extraction Of Coding and Regulatory Regions Based On Transcrmentioning
confidence: 99%